Effects of grab bar on utilized friction and dynamic stability when elderly people enter the bathtub. (August 2017) - Sekiguchi, Yusuke; Kato, Tomohisa; Honda, Keita; Kanetaka, Hiroyasu; Izumi, Shin-Ichi
Abstract: Background: The effect of the grab bar on dynamic stability when elderly people enter the bathtub remains unclear. The purpose of the present study is to examine the age-related effect of the grab bar on dynamic stability during lateral stepping over an obstacle when entering bathtub. Methods: Sixteen young, healthy adults and sixteen elderly adults participated. The subjects performed lateral stepping over an obstacle with and without vertical and horizontal bars. Displacement and velocity of the center of mass and utilized friction, which is the required coefficient of friction to avoid slipping, were simultaneously measured by a three-dimensional motion analysis system and two force plates. Findings: A post hoc test for two-way ANOVA revealed that velocity of the center of mass in the vertical direction ( p  < 0.05) and peak-to-peak values of the center of mass in the lateral ( p  < 0.05) and vertical directions ( p  < 0.05) with each grab bar were significantly slower and smaller than those without the grab bar in young and elderly people. Moreover, the utilized friction at push off of the trailing leg with the vertical bar in elderly people was lower ( p  < 0.05) than that in participants without the grab bar. Interpretation: The use of each grab bar while performing a lateral step over an obstacle may help maintaining balance in lateral and vertical directions. However, use of the vertical bar while lateral stepping over an object in elderly people may need low utilized friction to prevent slipping. Highlights: The use of a vertical bar in elderly participants reduced utilized friction. The use of a horizontal bar led to the smallest sway in a vertical direction. The use of each grab bar reduced sway in lateral and vertical directions.